STRATEGI ALIANSI QUADRILATERAL SECURITY DIALOGUE (QUAD) DALAM MENANGGAPI ESKALASI KONFLIK LAUT CHINA SELATAN (TAHUN 2020-2024) - Adila, Nisa; Renolafitri, Hendrini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Peace Corps is a United States instrument in Indonesia that focuses on English language teaching programs in rural areas of Indonesia, not only as a means of educational assistance but also as a tool of US foreign diplomacy. Through the concept of non-military, the United States seeks to build a positive image, strengthen bilateral relations, and spread values in partner countries such as Indonesia. This study analyzes the interests of the United States in Indonesia through the Peace Corps in 2021. This analysis uses a qualitative method with the Offensive Realism theory by John J. Mearsheimer, namely that a country will continue to strive to increase its power in strategic areas with military or non-military forces. This study also uses the concept of national interest from Donald E. Nuechterlain. The result of the study show that the United States utilizes the Peace Corps as a strategic instrument to achieve its interests, particularly ideological ones through the dissemination of individualistic and open values, as well as world order interests through strengthening its influence in Southeast Asia. The Peace Corps is also part of the United States' nation-branding strategy on the global stage. Thus, the Peace Corps program is not merely a form of humanitarian cooperation, but rather reflects the United States' foreign policy interests, implemented through a long-term social and cultural approach. Keywords: Peace Corps, National Interest, Soft Power, offensive Realism, Nation Branding